Pediatric Responses to Fundamental and Formant Frequency Altered Auditory Feedback: A Scoping Review - Coughler, Caitlin; Quinn de Launay, Keelia L.; Purcell, David W.; Oram Cardy, Janis; Beal, Deryk S. (Frontiers in Human Neuroscience, 2022)
Purpose: The ability to hear ourselves speak has been shown to play an important role in the development and maintenance of fluent and coherent speech. Despite this, little is known about the developing speech motor control system throughout childhood, in particular if and how postural and phonemic settings may differ throughout development. The current scoping review explored how investigations of individual responses to frequency altered auditory feedback have been used to provide insight into the development of auditory feedback control and sensorimotor learning in pediatric populations. Method: Six academic databases were systematically searched for studies that included (a) real-time perturbation of frequency in auditory input, (b) an analysis of immediate effects on speech, and (c) participants aged 18 years or younger. Results: Twenty-three articles met inclusion criteria. Manipulations included fundamental frequency (9 studies), formant frequency (12), frequency centroid of fricatives (1), and both fundamental and formant frequencies (1). Findings indicated that children above four years generally compensated in the opposite direction of the manipulation, however, in several cases not as effectively as adults. Conclusion: Overall, a wide range of manipulations and designs were used and results varied greatly, making generalization challenging. Differences found between age groups in the features of the compensatory vocal responses suggest that maturational changes may be occurring in the speech motor control system, affecting the extent to which auditory feedback is used to modify internal motor representations. Varied findings suggest postural control develops prior to phonemic control. Future studies with multiple outcome measures, manipulations, and more expansive age ranges are needed to elucidate findings.